The prevailing leadership styles among heads of academic departments in Palestinian university colleges from the perspective of their faculty members (Palestine Technical College Journal for Research and Studies, 2022)
The study aimed to identify the leadership styles prevalent among the heads of academic departments in Palestinian university colleges from the perspective of their faculty members, and to determine whether there are statistically significant differences at the level of significance (α ≤ 0.05) between average degrees of the sample individuals' estimation of the leadership styles prevalent among heads of academic departments in university colleges in Palestine attributed to the variables (gender, years of service, academic qualification, and college). Depending on the descriptive analytical approach and reference to previous literature, a questionnaire was designed consisting of (34) items distributed on (5) axes: (Democratic leadership style, autocratic leadership style, laissez-faire leadership style, transformational leadership style, and transactional leadership style). After verifying the questionnaire's validity and reliability, it was applied to a random sample of 277 faculty members. The study found that the overall degrees of estimation for the leadership styles prevalent among the heads of academic departments in university colleges in Palestine from the perspective of their faculty members were "high." The domain (laissez-faire leadership style) ranked first, with a "high" degree of estimation, followed by the domain (transformational leadership style), with a "high" degree of estimation as well, then the domain (democratic leadership style) with a "medium" degree of estimation, followed by the domain (autocratic leadership style), with a "medium" degree of estimation as well, and finally the domain (transactional leadership style) with a "medium" degree of estimation as well. The findings also revealed that there were no statistically significant differences at the significance level (α ≤ 0.05) between the average degrees of estimation of the sample individuals regarding the leadership styles prevalent among academic department heads that could be attributed to the variables (gender, years of service, and academic qualification), but there were statistically significant differences that could be attributed to the college variable, in favor of the University College of Applied Sciences. The study recommended working to urge the heads of academic departments in Palestinian university colleges to adopt modern leadership styles, especially democracy, transactional, and transformational, and to avoid practicing authoritarian and laissez-faire leadership styles.
Keywords: leadership styles; academic departments; university colleges; Palestine